Neuroscience-Based Information and Communication Technologies Development in Elementary School Mathematics through Games: A Case Study Evaluation - Marcos Procopio; Raquel Fernández-Cézar; Leandra Fernandes-Procopio; Benito Yánez-Araque (MDPI AG, 2024)
Universities play a pivotal role in knowledge production and in transforming teaching methodologies across various subjects. This research is a case study detailing the pedagogical implementation of a game-based methodological approach in a dual-degree program for primary and early childhood education teachers. The focus is on integrating information and communication technologies (ICT) tools for mathematics, specifically Scratch and GeoGebra, underpinned by principles of neuroscience. Based on a sample of 28 students, this study adopted game-based learning (GBL) in mathematics exercises, aimed at equipping student-teachers with strategies for educating future students (ages 7 to 11) in the 3rd to the 6th grade. Key areas of focus included plane and spatial geometry, requiring student-teachers to design game-like activities, emulating the problem-solving approaches of children. The culmination of this study involved presentations by the student-teachers, demonstrating how neuroscience principles can enhance the creation of educational games for primary school students. The findings highlight a significant divergence between the reality of teaching mathematics and the preconceived notions held by the student-teachers. This study opens avenues for integrating neuroscience into education, particularly through GBL, but also highlights the need for comprehensive understanding and application of neuroscientific principles to maximize learning outcomes.